Effect of Industrial Action on Small and Medium-Scale Businesses Productivity and Operations - Abdullahi Temitope Yusuf; Sule Magaji; Lateef Shariffdeen Olamilekan (Research Synergy Foundation, 2022)
This study examines the effect of industrial action on small and medium-scale businesses (SMEs) productivity and operations. To achieve this, the study examines the effect of the Academic Staff Union of Universities (ASUU) strike on SMEs in and around the Federal University of Lafia (FULafia) Nasarawa. The study uses the Taro-Yamani Formula to determine the sample size. Questionnaires were used to collect data, and the Logit regression method was employed for the analysis. The result revealed that the ASUU strike has a negative and significant impact on SME operations in and around FULafia. Also, it reveals that the ASUU strike has an insignificant negative impact on SMEs' productivity in and around FULafia. The study, therefore, recommends that the government and other stakeholders should comply with whatever agreement is made with the striking union (ASUU) to avert strikes, as this not only cripples the academic calendar but also affects businesses and other economic activities within the environs of the universities.